Дослідження та аналіз прогнозних графіків електричного навантаження Об'єднаної енергосистеми України та показників їх форми - Kobrin P.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
In the article research and analysis of the perspective graphs of the electric loading of the United energy system of Ukraine are given got by the form reflections method.